A review of the Rotokawa Geothermal Field, New Zealand. (January 2016) - McNamara, David Daniel; Sewell, Steven; Buscarlet, Etienne; Wallis, Irene C.
Highlights: Structurally controlled fluid flow is important in the Rotokawa Geothermal Field. Alteration mineralogy reveals complex evolution of the field conditions over time. Fluids and silica deposits contain high metal concentrations. Fluid interaction between multiple aquifers results in various chemical processes. Microseismicity has been a valuable reservoir monitoring tool. Abstract: The Rotokawa Geothermal Field of New Zealand has seen significant development over the last 20 years and has been the study site for new and innovative geological and geothermal research. This includes the one of the first direct data acquisition and characterisation of subsurface structure and stress properties via borehole image logs, a robust study of the magneto-telluric and micro-seismicity of the field, and the establishment of a comprehensive mode of the field's variable fluid chemistry. This paper reviews published material on the geology, geophysics, and fluid chemistry of this field, as well as summarises the development history and sustainability of this nationally important energy resource.